ANALISIS TINGKAT LITERASI KEUANGAN SYARIAH MASYARAKAT SANGKANAYU MREBET KABUPATEN PURBALINGGA - Ubaidillah Ubaidillah; Mia Nur Hasanah (Program Studi Administrasi Bisnis, 2021)
This study aims to determine the level of Islamic financial literacy of the people of Sangkanyu Mrebet Purbalingga Regency. This research uses descriptive quantitative analysis techniques. The types of data used are primary data and secondary data. Primary data were obtained from the results of field research by distributing questionnaires to the village community. Secondary data are obtained from documents and other sources related to research. Islamic financial literacy is the knowledge or understanding that individuals have of Islamic finance such as knowing Islamic financial products and services so that they can make financial decisions in accordance with Islamic principles. The results of this study indicate that the level of Islamic financial literacy of the people of Sangkanayu is 56.88% or it can be said that the level of Islamic financial literacy belongs to the low category (<60%).